Pengaruh Kompetensi Tenaga Pendidik Terhadap Kualitas Pendidikan Madrasah di Sumatera Barat - Silvia Marlina; Nofia Sherli; Iswantir (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to determine the competence of private Madrasah Ibtidaiyah (MIS) educators in Piladang and their effect on the quality of education in MIS Piladang. This type of research is ex post facto research using a questionnaire with quantitative analysis methods. The data analysis technique in this research is descriptive statistical analysis. Based on the results of descriptive statistical analysis, it shows that the competence of educators is in the medium category, with a percentage of 90% competent and 10% incompetent. This explains that there is a significant influence between the influence of educator competence on the quality of educators at MIS Piladang.